2018
DOI: 10.1021/acs.jpcb.8b09910
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Coupling Effects in the Infrared Spectra of Liquid Water

Abstract: Effects in the Infrared Spectra of Liquid Water. ChemRxiv. Preprint.A quantitative characterization of intermolecular and intramolecular couplings that modulate the OH-stretch vibrational band in liquid water has so far remained elusive. Here, we take up this challenge by combining the centroid molecular dynamics (CMD) formalism, which accounts for nuclear quantum effects, with the MB-pol potential energy function, which accurately reproduces the properties of water across all phases, to model the infrared (IR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 67 publications
1
80
0
Order By: Relevance
“…Moreover, a shoulder around ∼2300 cm −1 on the lefthand side of the peak is identified in the stretching band in experimental spectra of water. According to recent theoretical analyses 41,42 , this shoulder feature is attributed to the so-called Fermi resonance which describes the spectral enhancement due to the intramolecular vibrational coupling between the OD stretching mode and the overtone of bending mode. At both PBE and SCAN levels of studies, the shoulder appears roughly at the same position around 2300 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a shoulder around ∼2300 cm −1 on the lefthand side of the peak is identified in the stretching band in experimental spectra of water. According to recent theoretical analyses 41,42 , this shoulder feature is attributed to the so-called Fermi resonance which describes the spectral enhancement due to the intramolecular vibrational coupling between the OD stretching mode and the overtone of bending mode. At both PBE and SCAN levels of studies, the shoulder appears roughly at the same position around 2300 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, one may expect that the hybrid functional SCAN0 mitigates the self-interaction error in DFT, and brings the calculated IR spectra closer to the experiments. Furthermore, recent studies 42,46,47 suggested that nuclear quantum ef-fects due to light protons play a crucial role in obtaining accurate liquid water properties. The role played by quantum nuclei awaits the future investigation which is likely to broaden the spectral features and slightly reduce the frequencies of stretching band due to the delocalized protons.…”
Section: Discussionmentioning
confidence: 99%
“…imaginary-time Feynman paths) [33][34][35] to describe the quantum Boltzmann statistics, and obtains classical trajectories from a Liouvillian that conserves the ring-polymer phase-space density. These 'ring-polymer methods' include centroid molecular dynamics (CMD) [20][21][22][23][24][25] and (thermostatted) ring-polymer molecular dynamics ((T)RPMD). 18,[26][27][28][29][30][31][32] Unlike LSC-IVR, the ring-polymer methods conserve the quantum Boltzmann distribution by construction.…”
Section: Introductionmentioning
confidence: 99%
“…Within the MB-nrg framework, the water-water interactions are described by the MB-pol PEF, [9][10][11] which has been shown to correctly reproduce the properties of water 34,35 from small clusters in the gas phase, [36][37][38][39][40][41][42][43][44][45][46][47][48] to bulk water, [49][50][51][52] the air/water interface, [53][54][55][56] and ice. [57][58][59] The interactions between Cs + ions and water molecules are described through the MBE of Eq.…”
Section: A Mb-nrg Potential Energy Functionsmentioning
confidence: 99%